Biomarcadores precoces da injúria renal no envenenamento experimental induzido pela serpente colombiana Bothrops ayerbei em ratos - Reyes, Mayra Alejandra Velasco (2017)
The snake poisoning represents a public health problem, which is characterized by several systemic pathophysiologies, among which acute renal injury (AKI) is the most important. The pathogenesis of AKI induced by Botrópico poisoning is multifactorial and tends to be associated with direct nephrotoxicity, disseminated vascular coagulation and the activity of proteolytic enzymes that act on the structures of the kidney. In the state of Cauca in Colombia the snake Botrhops ayerbei was recognized as a new species through the morphological description and molecular characterization of its venom, considering the latter as a valuable signature for the identification of species and the properties of the venom. Therefore, the purpose of this work is to characterize the renal effects of venom of B. ayerbei (VBa), the present study evaluated biochemical parameters associated with renal function, oxidative profile and antioxidant activity, making a comparison with early biomarker of renal injury through gene transcription RT-PCR, and histopathological analysis. For this, 250-300g Wistar rats (150/14 protocol) were used, divided into three times 8, 16 and 24 hours each with two control (PBS) and treated groups (75% DVB of VBa). Thus, it was observed that poisoning by intraperitoneal inoculation of VBa promotes biochemical changes associated at the onset with direct injury of the venom on renal structures, causing an increase in plasma uric acid (8h: 1,220 ± 0,2061 μg / dL) and urinary (8h: 5,600 ± 0,230 μg / dL), followed by proteinuria (8h: 17,920 ± 0,807 μg / dL), decreased glomerular filtration rate (GFR) (8h: 0.9211 ± 0.2131 mL / min / 100g) , And increased clearance of free water (8h: -0.013 ± 0.003 mL / min), as well as increased urine osmolality (8h: 625.8 ± 33.27 Mmol / kg). An increase in urine urea concentrations (16h: 31,120 ± 1,866 μg / dL) and urinary creatinine (24h: 54,890 ± 3,360 μg / dL) was observed, with a decrease in the osmolality clearance (16h: 317.8 ± 26 , 05 Mmol / kg) and an increase in the Na + excretion fraction (16h: 4.552 ± 0.204%) and the RFG (24h: 0.7415 ± 0.0717 mL / min / 100g). (24h: 78.75 ± 3.059 μg / mg prot.) And renal cell damage was found by expression of renal biomarkers such as: renal injury-1 molecule (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL). In addition, pro-inflammatory cytokines such as interleukin-18 (IL-18), interleukin-1 beta (IL-1β) and chemotactic peptide-1 for monocytes (MCP-1) were found to act as adjuvants in the injury process Thus, VBa does not alter plasma parameters associated with AKI, but causes hemorrhagic processes that affect the blood circulation with extravasation, which could cause hypovolemic and consequent decrease of RFG, followed by a regulation in the excretion of substances. Compared with the results of molecular biology, renal cell damage has been proven, and inflammatory processes that may promote renal damage have been developed. We conclude that the VBa venom promotes changes in kidney damage as demonstrated by molecular biology, and not by biochemical tests, demonstrating that the use of early biomarkers is necessary for the understanding of renal pathophysiology generated by snake poisoning.